A case of angiosarcoma of the nasal cavity - G., Mahesh Santhraya; Pannen, Devan Poothatta; M. S., Kishor Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Angiosarcoma of the nasal cavity is extremely uncommon accounting for less than 0.1% of all sinonasal malignancies. Here we report a case of angiosarcoma of nasal cavity. A 45 year old male patient with c/o right sided nasal bleeding since 20days, on examination showed mass in nasal cavity. Patient underwent septoplasty with right inferior turbinectomy with submucosal diathermy. The histological examination showed features of angiosarcoma epitheloid variation of nasal cavity, diagnosis was confirmed by immunohistological stain with factor CD 31 and cytokeratin.